(untitled) (Bangladesh Journal of Botany, 2012)
Relationships among 14 Crocus L. taxa such as, C. ancyrensis (Herbert) Maw, C. baytopiorum Mathew, C. biflorus Miller ssp. crewei (Hook.) Mathew, C. biflorus ssp. isauricus (Siehe ex Bowles) Mathew, C. biflorus ssp. nubigena (Herbert) Mathew, C. biflorus ssp. pseudonubigena Mathew, C. cancellatus Herbert ssp. cancellatus, C. cancellatus ssp. damascenus (Herb ert) Mathew, C. cancellatus ssp. lycius Mathew, C. cancellatus ssp. mazziaricus (Herbert) Mathew, C. cancellatus ssp. pamphylicus Mathew, C. pestalozzae Boiss., C. reticulatus Steven ex Adams ssp. hittiticus (T. Baytop & Mathew) Mathew and C. sieheanus Barr ex Burtt collected from different two locations of Turkey have been investigated using 11 anatomic leaves characters. These taxa are endemic (except ssp. damascenus) and rare in Turkey. The anatomical variations in the cross sections of the leaf parts of the taxa were ascertained by statistical methods. It appears that the length and breadth measurements of palisade and spongy parenchyma cells, trachea diameter and cuticle thickness are important leaf anatomical characters that show variation in relation to altitudes. Key words: Crocus; Endemic; Leaf anatomy; Relationships DOI: http://dx.doi.org/10.3329/bjb.v40i2.9771 Bangladesh J. Bot. 40(2): 155-162, 2011 (December)